Genetic diversity of Staphylococcus aureus wall teichoic acid glycosyltransferases affects immune recognition. Issue 12 (7th December 2022) - Tamminga, Sara M.; Völpel, Simon L.; Schipper, Kim; Stehle, Thilo; Pannekoek, Yvonne; van Sorge, Nina M.
Abstract : Staphylococcus aureus is a leading cause of skin and soft tissue infections and systemic infections. Wall teichoic acids (WTAs) are cell wall-anchored glycopolymers that are important for S. aureus nasal colonization, phage-mediated horizontal gene transfer, and antibiotic resistance. WTAs consist of a polymerized ribitol phosphate (RboP) chain that can be glycosylated with N -acetylglucosamine (GlcNAc) by three glycosyltransferases: TarS, TarM, and TarP. TarS and TarP modify WTA with β-linked GlcNAc at the C-4 (β1, 4-GlcNAc) and the C-3 position (β1, 3-GlcNAc) of the RboP subunit, respectively, whereas TarM modifies WTA with α-linked GlcNAc at the C-4 position (α1, 4-GlcNAc). Importantly, these WTA glycosylation patterns impact immune recognition and clearance of S. aureus . Previous studies suggest that tarS is near-universally present within the S. aureus population, whereas a smaller proportion co-contain either tarM or tarP . To gain more insight into the presence and genetic variation of tarS, tarM and tarP in the S. aureus population, we analysed a collection of 25 652 S . aureus genomes within the PubMLST database. Over 99 % of isolates contained tarS . Co-presence of tarS / tarM or tarS / tarP occurred in 37 and 7 % of isolates, respectively, and was associated with specific S. aureus clonal complexes. We also identified 26 isolates (0.1 %) that contained all three glycosyltransferase genes. At sequence level, we identified tar alleles with amino acid substitutions in critical enzymatic residues or with premature stop codons. Several tar variants were expressed in a S. aureus tar -negative strain. Analysis using specific monoclonal antibodies and human langerin showed that WTA glycosylation was severely attenuated or absent. Overall, our data provide a broad overview of the genetic diversity of the three WTA glycosyltransferases in the S. aureus population and the functional consequences for immune recognition.